Proposition for Speculative Recipes - Pavoni, A. (International Symposium: Cookbooks: Past, Present and Future, 2019)
Taking up the Symposium’s challenge, this paper reflects on the future of cookbooks by proposing the notion of ‘speculative recipe’, as a way to reconfigure the recipe-form, from a normative set of how-to instructions that discipline cooking into a procedure aimed to produce a standardised result; to an aesthetic-political tool that allows to sense and explore the complexity of contemporary food politics. Fredric Jameson (2007) once argued that peculiar to modernity is the separation of experience from its structural conditions of possibility– think about the imperceptible gap between the taste of a strong coffee in a Victorian London pub, and the violent structures of power and exploitation that allowed for such experience to take place at all. In today’s globalised gastro-culture, the split between the practices of cooking and tasting food, and the forces, structures and power relations that shape the way food is produced, distributed and consumed; keeps widening and multiplying. Recipes are normally blind to this gap. Framed within an ideology of measurability and repeatability, they tend to ossify both the practice of cooking and the parameters of taste, invisibilising the complex socio-political ecology out of which these emerge (Haden, 2011). Likewise, the contemporary mediatisation of recipes via cooking shows has a further de-materialising effect on ‘the concrete, real and material experience of both cooking and consuming the food, in favour of its media spectacularisation’ (Perullo, 2018). This paper proposes to disentangle recipes both from their parochial entrapment into bourgeois enjoyment, and from their normatively atrophying ideology. A chilli sauce that materialises the violence of financial capitalism; a strawberry jam that rethinks hospitality and xenophobia; a foodstagramming recipe that frames contemporary food porn (see Pavoni et al., 2018): thought such examples as these, the paper proposes the notion of speculative recipe, as a way through which the local and phenomenological experience of cooking and tasting may become a way to sense and explore the position that this very experience occupies with respect the wider socio-political structures, forces and relation.